WPŁYW DYREKTYW I ROZPORZĄDZEŃ UNII EUROPEJSKIEJ NA POLSKIE PRAWO PODATKOWE - Bernat, Rafał (Zeszyty Prawnicze, 2016)
The Impact of European Union Directives and Regulations on Polish Tax Law Summary The subject of this article are the methods used to align Polish tax regulations with EU law and the level of alignment achieved. The author examines aspects of tax law to discuss the procedures EU member states use to issue and apply EU regulations and directives and the influence of EU legislation on the jurisdictive practice of the Polish administrative courts.